Tjatatan Mengenai Stratigraphy Pegunungan Karangbolong, Djawa Tengah - H.D. Tjia (Journal of Mathematical and Fundamental Sciences, 1961)
The Karangbolong Mountains belong to the zone of Southern Mountains in Java. The former consists of three series rocks, the oldest being the "Old Andesite" Formation composed of andesitic eruptive and intrusive of oligicene to aquitanian age, uncomprotably overlain by the Karangbolong Limestone Member of Tertiary f1-3. Toward the north the upper most limestone beds interlinger with beds of the Marl-tuff Member of Tertiary f3. After this time marine sedimentation in this area came to a halt. Both the Karangbolong Limestone and the Marl-tuff members together form the Karangbolong Marine Formation.